Sakralitas Kue Adat Tamo Untuk Inklusivitas Keagamaan Masyarakat di Sanger, Sulawesi Utara - Tony Tampake; Janhard Katampuge (Indonesian Journal of Religion and Society, 2022)
Sanger community in North Sulawesi has one type of sacred food called Kue Adat Tamo. The food has become medium and symbol of Sanger community's religious worship. The sacredness of Tamo Traditional Cake is internalized and expressed in an annual Tulude ritual forming their inclusive social religious identity. Therefore, this paper aims to answer the ontological question about the understanding of Sanger community in Tuma towards the sacredness of Tamo Traditional Cake that becomes their collective expression and inclusiveness. To answer this question, the research was conducted using a qualitative approach and the type of ethnographic research as well as data collection techniques through interviews and observations carried out in Tuma Sanger Village. The result of the study indicates that the sacredness of Tamo Traditional Cake lies in the collective admiration and respect of Tuma community in Sanger for Ghenggonalangi which is symbolically expressed in the community's annual thanksgiving party known as Tulude. Based on these findings, the main argument of this paper is that the sacredness of Tamo Traditional Cake is rooted in the acculturation of religious culture and the social reality of Tuma Sanger community.